Evaluation of cognitive restructuring for post-traumatic stress disorder in people with severe mental illness. (June 2015) - Mueser, Kim T.; Gottlieb, Jennifer D.; Xie, Haiyi; Lu, Weili; Yanos, Philip T.; Rosenberg, Stanley D.; Silverstein, Steven M.; Duva, Stephanie Marcello; Minsky, Shula; Wolfe, Rosemarie S.; McHugo, Gregory J.
Abstract : Background: A cognitive–behavioural therapy (CBT) programme designed for post-traumatic stress disorder (PTSD) in people with severe mental illness, including breathing retraining, education and cognitive restructuring, was shown to be more effective than usual services. Aims: To evaluate the incremental benefit of adding cognitive restructuring to the breathing retraining and education components of the CBT programme (trial registration: clinicaltrials.gov identifier: NCT00494650). Method: In all, 201 people with severe mental illness and PTSD were randomised to 12- to 16-session CBT or a 3-session brief treatment programme (breathing retraining and education). The primary outcome was PTSD symptom severity. Secondary outcomes were PTSD diagnosis, other symptoms, functioning and quality of life. Results: There was greater improvement in PTSD symptoms and functioning in the CBT group than in the brief treatment group, with both groups improving on other outcomes and effects maintained 1-year post-treatment. Conclusions: Cognitive restructuring has a significant impact beyond breathing retraining and education in the CBT programme, reducing PTSD symptoms and improving functioning in people with severe mental illness.